Commutators of the Bilinear Hardy Operator on Herz Type Spaces with Variable Exponents - Shengrong Wang; Jingshi Xu (Journal of Function Spaces)
In this paper, we obtain the boundedness of bilinear commutators generated by the bilinear Hardy operator and BMO functions on products of Herz spaces and Herz-Morrey spaces with variable exponents.